2021
DOI: 10.1136/bmjopen-2021-049370
|View full text |Cite
|
Sign up to set email alerts
|

Decision (not) to disclose mental health conditions or substance abuse in the work environment: a multiperspective focus group study within the military

Abstract: ObjectivesMany workers in high-risk occupations, such as soldiers, are exposed to stressors at work, increasing their risk of developing mental health conditions and substance abuse (MHC/SA). Disclosure can lead to both positive (eg, support) and negative (eg, discrimination) work outcomes, and therefore, both disclosure and non-disclosure can affect health, well-being and sustainable employment, making it a complex dilemma. The objective is to study barriers to and facilitators for disclosure in the military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(59 citation statements)
references
References 42 publications
(57 reference statements)
2
57
0
Order By: Relevance
“…This is important, as 27% of Dutch workers does not disclose mental illness in the work environment, and therefore by definition also misses out on workplace support and accommodations that may be important to stay at work. Finally, the findings add to the growing literature that a safe workplace atmosphere, where workers with health problems are supported rather than excluded, is not only highly important for disclosure, but ultimately also for workers’ sustainable employment, health and well-being [ 1 , 19 , 49 , 51 ]…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This is important, as 27% of Dutch workers does not disclose mental illness in the work environment, and therefore by definition also misses out on workplace support and accommodations that may be important to stay at work. Finally, the findings add to the growing literature that a safe workplace atmosphere, where workers with health problems are supported rather than excluded, is not only highly important for disclosure, but ultimately also for workers’ sustainable employment, health and well-being [ 1 , 19 , 49 , 51 ]…”
Section: Discussionmentioning
confidence: 73%
“…Future studies should also focus on actual outcomes of workplace disclosure. Nevertheless, perceptions are important predictors of actual behavior [ 48 ], and many workers fear that disclosure will lead to discrimination (e.g., job loss, no contract renewal, lower wages) [ 1 , 30 , 49 ]. Whether or not these perceptions are true, they can influence workers’ disclosure behavior (non-disclosure).…”
Section: Discussionmentioning
confidence: 99%
“…However, a longitudinal study among unemployed people showed that those who were more reluctant to disclose their MI to (potential new) employers, were more likely to have found a job after six months [23]. Additionally, disclosure to a supervisor can lead to stigma and discrimination [24][25][26]. For example, of those who reported a negative disclosure experience in a study among Dutch workers, a quarter reported that they had been treated differently due to their disclosure [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that the decision to disclose or not is an even more prominent dilemma in high-risk occupations, such as the military. People in military professions are expected to be strong, and not to show weakness, possibly making disclosure harder [21,24,32]. For example, in a study in the German military, a soldier indicated "If I hear that this battalion commander is mentally ill … as a subordinate, honestly, I'd say 'What kind of guy is that?'…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation